IDENTIFIKASI KESALAHAN PENYUSUNAN SKRIPSI MINI DALAM MATA KULIAH·PENULISAN KARYA ILMIAH MAHASISWA FAKULTAS ILMU KEOLAHRAGAAN - Yustinus Sukarmin (Jurnal Cakrawala Pendidikan, 2008)
This research discusses. the mini thesis development process which wasconducted by. Sports Science Faculty students· in the Scientific Paper Writingcourse. The. aimof this research is to· identify the·mistakes made by the students inthe mini thesis development..This research was· a descriptive study on mistakes.The. population consistedof 237 mini theses written by students of the. Faculty ofSports.. Science in the Scientific Paper Writing course in the academic year of2006/2007. The sample consisted of100 mini theses selected by using theproportional sampling technique. The data collection instruments were a check-listand a table developed from Pedoman Tugas Akhir UNY 2003 (Thesis GuidelinesYogyakarta State University2003). The data were analyzed by using the descriptivequantitative technique involving percentage. The results of this research showedthat in the mini thesis writing, technically, students made mistakes mostly ingrammar, spelling and punctuation, .writing rules,and content. In the writingorganization,the most common mistakes were made in the middle part, while themistakesin the introductory part and those in the closing were evenly balanced.